Alignment of Continuous Auditory and Visual Distractor Stimuli Is Leading to an Increased Performance - Mühlberg, Stefanie; Müller, Matthias M. (Frontiers in Psychology, 2020)
Information across different senses can affect our behavior in both positive and negative ways. Stimuli aligned with a target stimulus can lead to improved behavioral performances, while competing, transient stimuli often negatively affect our task performance. But what about subtle changes in task-irrelevant multisensory stimuli? Within this experiment we tested the effect of the alignment of subtle auditory and visual distractor stimuli on the performance of detection and discrimination tasks respectively. Participants performed either a detection or a discrimination task on a centrally presented Gabor patch, while being simultaneously subjected to a random dot kinematogram, which alternated its color from green to red with a frequency of 7.5 Hz and a continuous tone, which was either a frequency modulated pure tone for the audiovisual congruent and incongruent conditions or white noise for the visual control condition. While the modulation frequency of the pure tone initially differed from the modulation frequency of the random dot kinematogram, the modulation frequencies of both stimuli could align after a variable delay, and we measured accuracy and reaction times around the possible alignment time. We found increases in accuracy for the audiovisual congruent condition suggesting subtle alignments of multisensory background stimuli can increase performance on the current task.